Construction of the Enterococcal Strain Expressing Immunogenic Fragment of SARS-Cov-2 Virus - Suvorov, Alexander; Gupalova, Tatiana; Desheva, Yulia; Kramskaya, Tatiana; Bormotova, Elena; Koroleva, Irina; Kopteva, Olga; Leontieva, Galina (Frontiers in Pharmacology, 2022)
Contemporary SARS-Cov-2 pandemic besides it dramatic global influence on the human race including health care systems, economies and political decisions opened a window for the global experiment with human vaccination employing vaccines made by the novel genetic technologies which were successfully introduced into the market due to the changes in regulations. However, all these vaccines being immunogenic and protective rely predominantly on IgG response after two or more than two injections. At the same time, many of these vaccines require handling at strict low temperature conditions. This makes contemporary vaccines relatively hard to administer. It is now widely accepted oral or nasal immunization provide protection against the infections on mucosal surfaces – the gate of infection with predominantly IgA response. Some genetically modified bacteria, including probiotics, represent attractive vehicles for oral or nasal mucosal delivery of therapeutic molecules. Probiotic-based vaccines for mucous membranes are easy to produce in large quantities; they have low cost, and provide quite a long T-cell memory. The gut IgA response to oral vaccines is highly synchronized and strongly oligoclonal. Here we present a study of construction of the novel SARS-Cov-2 vaccine candidate employing the gene fragment of S1 SARS-Cov-2 gene, which was selected after epitope analysis, cloned and expressed in E.coli and was tested for immunogenicity in mice and rabbits. This DNA fragment was inserted in frame into major pili protein gene with d2 domain of enterococcal operon encoding for pili. Probiotic strain Enterococcus faecium L3 having long history of usage for consumption in different dysbiotic conditions including IBS, chronic gastritis, encephalomyelitis, H.pylori infections and some other health conditions was used as bacterial vector. The DNA sequencing proved the presence of the insert in enterococcal genome. RNA transcription, immunoprecipitation and immune electron microscopy with human sera obtained from the SARS-Cov-2 patients demonstrated expression of SARS-Cov-2 antigens in bacteriaTaken together the data obtained allowed considering this genetically modified probiotic strain as an interesting candidate of vaccine against SARS-Cov-2.